Free choice of healthcare providers in the Netherlands is both a goal in itself and a precondition: modelling the policy assumptions underlying the promotion of patient choice through documentary analysis and interviews - Victoor Aafke; Friele Roland D; Delnoij Diana MJ; Rademakers Jany JDJM (BMC, 2012)
Abstract Background In the Netherlands in 2006, a health insurance system reform took place in which regulated competition between insurers and providers is key. In this context, the government placed greater emphasis on patients being able to choose health insurers and providers as a precondition for competition. Patient choice became an instrument instead of solely a goal in itself. In the current study, we investigated the concept of 'patient choice' of healthcare providers, as postulated in the supporting documentation for this reform, because we wanted to try to understand the assumptions policy makers had regarding patient choice of healthcare providers. Methods We searched policy documents for assumptions made by policy makers about patient choice of healthcare providers that underlie the health insurance system reform. Additionally, we held interviews with people who were involved in or closely followed the reform. Results Our study shows that the government paid much more attention to the instrumental goal of patient choice. Patients are assumed to be able to choose a provider rationally if a number of conditions are satisfied, e.g. the availability of enough comparative information. To help ensure those conditions were met, the Dutch government and other parties implemented a variety of supporting instruments. Conclusions Various instruments have been put in place to ensure that patients can act as consumers on the healthcare market. Much less attention has been paid to the willingness and ability of patients to choose, i.e. choice as a value. There was also relatively little attention paid to the consequences on equity of outcomes if some patient groups are less inclined or able to choose actively.